Kimotopia: The use of a serious game for learning about cancer - Feitosa, Juliana da Costa; Guimarães, Marcelo Paiva; Ferreira Brega, José Remo (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
The present work presents a serious game, called Kimotopia, developed with the intention of teaching about oncological medical treatments for children and adolescents with cancer. The methodology has been determined according to techniques and specifications that make a serious game effective for health. Based on this, the game is presented and contains features that help players in the knowledge about their condition and the necessary medical procedures. With the application of the game, satisfactory results were obtained regarding the immersion and interactivity of the game.